Preparation and immunogenicity evaluation of C-HapS-P6 fusion protein vaccine against nontypeable Haemophilus influenzae in mice - Nan Hu; Weifeng Li; Zihong Zhao; Yueli Chang; Cai Wang; Yutuo Zhang (Elsevier, 2024)
Nontypeable Haemophilus influenzae (NTHi) is the dominant pathogen in several infectious diseases. Currently the use of antibiotics is the main intervention to prevent NTHi infections, however with the emergence of drug resistant strains, it has compromised the treatment of respiratory infections with antibiotics. Therefore there is an urgent need to develop a safe and effective vaccine to prevent NTHi infections. We investigate the potential of C-HapS-P6 fusion protein as a vaccine for treating NTHi in murine models. PGEX-6P2/C-HapS-P6 fusion gene was constructed using overlap extension polymerase chain reaction. The recombined plasmid was transformed into Escherichia coli for protein expression. The mice were subjected to intraperitoneal immunization using purified antigens. Immunoglobulin (Ig) G in serum samples and IgA in nasal and lung lavage fluids were analyzed using enzyme-linked immunosorbent assay. Cytokine release and proliferation capacity of splenic lymphocytes in response to antigens were measured in vitro. The protective effect of the C-HapS-P6 protein against NTHi infection was evaluated by NTHi count and histological examination. The data showed that the C-HapS-P6 fusion protein increased significantly the levels of serum IgG and nasal and lung IgA, and promoted the release of interleukin (IL)-2, interferon-ϒ, IL-4, IL-5, and IL-17 and the proliferation of splenic lymphocytes compared with C-HapS or P6 protein treatment alone. Moreover, C-HapS-P6 effectively reduced the NTHi colonization in the nasopharynx and lungs of mice. In conclusion, our results demonstrated that the C-HapS-P6 fusion protein vaccine can significantly enhance humoral and cell immune responses and effectively prevent against NTHi infection in the respiratory tract in murine models.